Britain and the Netherlands - Bromley, J. S. author. aut Link
V, 233 p. 6 illus.
Keywords: EXCEPT for chapter 8, an editorial foot-bridge across the con fused years which separate the Dutch Republic from the King dom of the Netherlands, the essays collected in this volume were originally read and discussed at meetings of Dutch and British historians held between 22 and 27 September 1969 in a number of delightful comers of Groningen and Friesland. That this con ference took place at all was due in the first instance to the initiative and organizing genius of the Instituut voor Geschiedenis of the University of Groningen: particular thanks are due to the Rector Magnificus and his colleagues of that illustrious place of learning. On behalf of those fortunate enough to take part, we also wish to place on record our deep gratitude for the benevolent assistance of the Netherlands Ministerie van Onderwijs, of the H. S. Kammingafonds and of the Groninger Universiteitsfonds. As our sub-title strives to hint, the conference papers were commissioned with a view to stimulating historical awareness of a problem which is increasingly forcing itself on the attention of contemporary statesmen, administrators, sociologists and others - indeed of all who value local character and the human scale in the age of mass communications and socialized government.